A CORRELATIONAL STUDY BETWEEN STUDENTS’ HABIT IN LISTENING ENGLISH SONG AND STUDENTS’ VOCABULARY MASTERY - Irpan Yulianto; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to determine the correlation that occurs between students’ habit in listening English song and vocabulary mastery of the eleventh grade students at MAN 1 Surakarta in the 2022/2023 academic year. Quantitative research with correlation method was applied in this research. The sample for this research was 32 students. The researcher used a questionnaire and a vocabulary test to gather the data. The findings of this study revealed a positive relationship between students' habit of listening to English songs and their vocabulary mastery. It is proven by the results after analyzing the two variables using the Person Product Moment formula, with the results of calculation of rxy 0.915 > rtable in the significant level of 0,05 = 0,349 and also 0,001 = 0.554. As a result, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It indicates that there is a positive correlation between students' habit of listening to English songs and their vocabulary knowledge. Thus, the higher the habit in listening English song, the better their vocabulary mastery. Keywords: Habit in Listening English Song, Vocabulary Mastery, Correlational Study